Youth Gangs, Violence and Social Respect - White, R. author. aut Link
VIII, 227 p.
Keywords: This is the first book dedicated to Australian youth gangs, exploring the subtleties and nuances of street life for young men and their quest for social respect. The key focus is on group violence and the ways in which the 'gang' provides a forum for the expression of this violence.